The relationship between works councils and firms’ further training provision in times of technological change - Lammers, Alexander [Verfasser]; Lukowski, Felix [Verfasser]; Weis, Kathrin [Verfasser] (My University, 2022)
“Participating in further training is strategically important for employees to ensure their employability. Particularly for employees in low-skilled jobs, works councils — firm-level organizations that represent employees — constitute an important employee advocacy instrument in European countries, such as France and Germany. With comprehensive co-determination rights, works councils can influence firms’ hiring policies, job design and career paths (e.g. promotions). Using German firm-level data, we empirically investigate the influence of works councils on firms’ training provision for employees in firms below and above the industry level of technology. The results show that works councils have a positive effect on the percentage of employees in general, and of employees in low-skilled jobs in particular, participating in training, but only for firms below the industry level of technology. These results show the importance of works councils in supporting training in such firms and enhancing the employment prospects of employees in low-skilled jobs. In contrast, firms above the industry level of technology invest in training with or without a works council, indicating that the training interests of employers and employees are aligned.“ (authors‘ abstract; BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; S 3.5.4 Sozialpartner; S 1.5.3 Betriebliche Weiterbildung; 370; Betrieb; Betriebsrat; Betriebliche Weiterbildung; Qualifizierung; Weiterbildungsverhalten; BIBB-Qualifizierungspanel